The use of building information modelling tools for effective waste management: A systematic review. Issue 6 (1st November 2022) - Liphadzi, Nhlalala Michelle; Musonda, Innocent; Onososen, Adetayo
Abstract: Construction waste needs to be managed to safeguard the environment. During the design stage in construction, BIM is usually used to demonstrate a virtual presentation of the building. The model can predict material that could be wasted. There is little research on "BIM for waste management". This study adopts a systematic literature review using the PRISMA model to evaluate extant studies on BIM for waste management. A systematic literature methodology is used to summarise the results of articles that have been previously published. Furthermore, this article identifies BIM tools that can be used for addressing the major problems caused by waste. Findings reveal the barriers to the implementation of BIM for waste management, which are; lack of BIM awareness, unavailability of resources, the lack of guarantee in the security of stored information, and uncertainties in legal policies. Three main BIM-based tools, which can be used for planning for effective waste management have been identified and discussed. The significance of this research is to raise awareness for BIM tools as an aid to effective waste management in construction. The study also points out future research areas that can be investigated to aid the implementation of BIM-based tools for waste management.